Low-Intensity Pulsed Ultrasound Treatment Selectively Stimulates Senescent Cells to Promote SASP Factors for Immune Cell Recruitment - Gwak, HyeRan; Hong, Seoyoung; Lee, Su Hyun; Kim, In Woo; Kim, Yonghan; Kim, Hyungmin; Pahk, Ki Joo; Kim, So Yeon (Blackwell Publishing Inc., 2025)
As emerging therapeutic strategies for aging and age-associated diseases, various biochemical approaches have been developed to selectively remove senescent cells, but how physical stimulus influences senescent cells and its possible application in senolytic therapy has not been reported yet. Here we developed a physical method to selectively stimulate senescent cells via low-intensity pulsed ultrasound (LIPUS) treatment. LIPUS stimulation did not affect the cell cycle, but selectively enhanced secretion of specific cytokines in senescent cells, known as the senescence-associated secretory phenotype (SASP), resulting in enhanced migration of monocytes/macrophages and upregulation of phagocytosis of senescent cells by M1 macrophage. We found that LIPUS stimulation selectively perturbed the cellular membrane structure in senescent cells, which led to activation of the intracellular reactive oxygen species-dependent p38-NF-κB signaling pathway. Using a UV-induced skin aging mouse model, we confirmed enhanced macrophage infiltration followed by reduced senescent cells after LIPUS treatment. Due to the advantages of ultrasound treatment, such as non-invasiveness, deep penetration capability, and easy application in clinical settings, we expect that our method can be applied to treat various senescence-associated diseases or combined with other established biochemical therapies to enhance efficacy.